A quantile‐based approach to improve homogenization of snow depth time series. (14th June 2022) - Resch, Gernot; Koch, Roland; Marty, Christoph; Chimani, Barbara; Begert, Michael; Buchmann, Moritz; Aschauer, Johannes; Schöner, Wolfgang
Abstract: Austrian observations of snow depth date back to 1895 and are thus among the longest available quantitative snow information from hydrometeorological networks worldwide. It is well known that such long‐term observations are prone to inhomogeneities, which may not only affect climatologies and trends, but derived products used in research or practice. While the reliability of available methods for detecting breaks in snow time series has been shown before and could also be confirmed by our work, we focused on improving the adjustment method. Conventional methods often refer to the median of difference or quotient series (INTERP), whereas our proposed method also uses a quantile‐wise adjustment (InterpQM), which is useful to minimize a bias on the tails of the frequency distribution. We demonstrated the success of the new method by using Swiss parallel snow depth observations. Errors of the analysed indicators could be reduced in 68% of the cases when compared with INTERP. The results were best for large snow depths, being up to 19% better. Overall, InterpQM was better in 75% of validation cases for the daily large, 72% of all observations and 56% of mean seasonal snow depth cases. We describe the performed homogenization procedure in detail, including quality control, gap filling, homogeneity testing, break detection, calculation of and improvements to the adjustment method. Our results show that snow depth time series generally have a lower number of breaks compared with station data of other climate variables. This underlines their high quality, even if measuring snow presents challenges. Using Austrian snow depth series as an example, the effects of the new adjustment method on trends were analysed using the Mann–Kendall and Sen's Slope. Homogenization may have a significant effect on derived trends: Two of the six adjusted series were changed from nonsignificant to significant and one vice versa. Abstract : For the purpose of improving the homogenization of snow depth time series, a quantile‐based correction scheme (InterpQM) was introduced. It was validated using a parallel snow dataset, where different scenarios simulating possible reasons for breaks were simulated. This approach generally provided better results than the method INTERP, especially for very large snow depths. The adjusted corrections to an Austrian dataset improved the trend analysis and had a significant impact on the derived trends for some of the stations.